The impact of ambitious fuel economy standards on the market uptake of electric vehicles and specific CO2 emissions. (December 2019) - Fritz, Markus; Plötz, Patrick; Funke, Simon A.
Abstract: Fuel economy regulation is a powerful instrument to reduce CO2 emissions of vehicles. CO2 emissions from transport have to be dramatically reduced to reach ambitious CO2 targets, but fuel economy standards below 75 gCO2 /km (72.8 MPG) cannot be reached with combustion engine vehicles but require plug-in electric vehicles (PEVs). However, the specific relationship between stringent fuel economy standards and PEV market share is unclear. Here, we analyse CO2 fleet targets in Europe where Regulation (EU) 2019/631 sets a target of 59.4 gCO2 /km (90.9 MPG) in 2030. We use data of 3.2 million records with model-specific car sales in Europe from 2010 to 2016 to project future sales and CO2 emissions of all major vehicle manufacturers. We analyse the required PEV sales for these manufacturers to fulfill the CO2 targets and compare them to the manufacturers' announced sales targets. Our results demonstrate that regulation's target leads to PEV sales shares between 27 and 41% in 2030. The lower value is required if all manufacturers only sell BEV and the upper if only PHEV. In conclusion, ambitious CO2 fleet regulation leads to fast market diffusion of PEVs, but the current regulation is less ambitious than car maker targets in 2025. Highlights: Analysis of the required PEV sales shares to fulfill manufacturers' CO2 targets. PEV sales model based on large public car sales data for Europe. Required PEV sales shares are well below manufacturers' own PEV sales targets. Ambitious CO2 fleet regulation leads to fast market diffusion of PEVs.